Curettage and bone grafting for simple bone cyst of humeral head in a young woman: arthroscopic approach and step towards minimal invasive surgery - Soni, Nirav G.; Jesalpura, Jaimeen P. (International Journal of Research in Orthopaedics, 2019)
The simple bone cyst (SBC) also called unicameral bone cyst is a tumor-like lesion of unknown cause, attributed to a local disturbance of the bone growth. Although the pathogenesis is still unknown, the lesion appears to be reactive or developmental . Traumatic etiology of simple bone cysts remains an enigma up to now. We present a case of 44 year old woman who came with c/o pain in right shoulder due to fall from vehicle 5 months back with X-ray and MRI both suggestive of cystic lesion over greater tuberosity humeral head . Patient was treated with arthroscopic curettage and bone grafting. In the last decade, however, there has been an exponential growth in the use of minimally invasive surgical techniques. This is particularly seen in the shoulder, where multiple arthroscopic and procedures have been described in the treatment of intra- and extra-articular pathologies.